2019
DOI: 10.35563/rmp.v3i1.94
|View full text |Cite
|
Sign up to set email alerts
|

Características del nivel de empatía hacia el paciente en internos de medicina de dos hospitales nacionales

Abstract: Objetivo: Determinar las características en el nivel de empatía hacia el paciente en los internos de Medicina del Hospital Nacional “Daniel Alcides Carrión” del callao (HNDAC) y del Hospital “María Auxiliadora” (HMA) de San Juan de Miraflores , su relación con la edad, sexo, tipo, procedencia de la universidad y el tipo de especialidad a seguir. Materiales y métodos: Se realizó un estudio transversal, descriptivo y de correlación en 131 internos de Medicina el 2012, usando la Escala de Empatía Médica de Jefferso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…In the Peruvian study conducted by Mayo et al (23), a medium level of empathy was observed, with a score of 112.88 (SD) 14.51. Similar findings were reported among medical interns in two national hospitals (112.27 ± 11.85) (47) and Mexican medical students (average score of 113) (48). These results are relatively favorable when compared to a study in Greece, where HCWs in public hospitals had an average score of 102 (SD) 16.2, bordering on the lower end of the empathy scale (11).…”
Section: Overall Empathy Analysissupporting
confidence: 83%
See 1 more Smart Citation
“…In the Peruvian study conducted by Mayo et al (23), a medium level of empathy was observed, with a score of 112.88 (SD) 14.51. Similar findings were reported among medical interns in two national hospitals (112.27 ± 11.85) (47) and Mexican medical students (average score of 113) (48). These results are relatively favorable when compared to a study in Greece, where HCWs in public hospitals had an average score of 102 (SD) 16.2, bordering on the lower end of the empathy scale (11).…”
Section: Overall Empathy Analysissupporting
confidence: 83%
“…In contrast, technology-focused specialties such as surgery necessitate diagnostic procedures before patient engagement. This trend was further supported by findings in medical interns from two Peruvian hospitals; those aspiring to patient-oriented specialties exhibited higher average empathy scores compared to their counterparts pursuing technology-oriented specialties (112.09 ± 12.420 vs. 111.84 ± 10.913, respectively) (47). Even Mexican students aspiring to specialize in surgery reported even lower empathy scores (108.8) (48).…”
Section: Empathy By Health Professionmentioning
confidence: 69%
“…43 De la misma manera el estudio de Remón-Torres también con una muestra de internos obtuvo una edad promedio de 25 años. 45 Con respecto al sexo en la presente investigación se obtuvo una predominancia del sexo femenino con un 53,5%(n=107) y del sexo masculino con 46,5%(n=93), siendo similar a los estudios realizados por Ulloque y col. en Argentina con una población femenina de 63,73% y masculina de 36,27% 10 .…”
Section: Discussionunclassified